Analisis Penyuntingan Aspek Kebahasan dalam Skripsi Diyah Ayu Cahyaningrum (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study examines written Indonesian language errors in Diyah Ayu Cahyaningrum's thesis. This research aims to: (1) find errors in linguistic aspects (spelling, diction, and morphology) in Diyah Ayu Cahyaningrum's thesis, (2) obtain a description of the relevance of the analysis of editing linguistic aspects in Diyah Ayu Cahyaningrum's thesis with the editing course in the Indonesian Language and Literature Education Study Program. The subject of this research is the thesis of a student named Diyah Ayu Cahyaningrum, while the object of this research is the analysis of editing the linguistic aspects in the thesis of a student named Diyah Ayu Cahyaningrum. The data in this study are in the form of text excerpts from theses that contain linguistic errors, both in aspects of spelling, diction, sentence structure, and interparagraph coherence. The data collection technique used by the researcher in this research is using documentation technique. This research uses a descriptive qualitative approach that aims to identify, describe, and analyze errors in the linguistic aspects of student thesis writing. The forms of errors in linguistic aspects found in this study include spelling (use of letters, word writing, and punctuation) with 10 errors, diction (nonstandard words) with 4 errors, and morphology (errors in adding the prefix di-) with 4 errors. The total number of errors found is 18 errors.